The effect of fibrinogen levels on three-month neurological recovery in acute ischemic stroke patients - Buket Özkara Yılmaz; Ramazan Şencan (Scientific Reports)
Abstract The present study aims to examine the relationship between post-stroke fibrinogen levels and long-term (three-month) prognosis in patients who had their first ischemic stroke and to determine the effect of fibrinogen levels on morbidity and mortality. A prospective study was carried out on 100 patients presenting with their first ischemic stroke at the Neurology Clinic of Gaziantep City Hospital. Stroke severity was examined utilizing the National Institutes of Health Stroke Scale (NIHSS) and the modified Rankin Scale (mRS) at initial admission and at third month post-stroke. Serum fibrinogen levels were recorded from routine blood tests, and the relationship between fibrinogen levels and clinical outcomes was analyzed statistically. Significant positive correlations were observed between fibrinogen levels and stroke severity and outcomes. Fibrinogen levels were associated with NIHSS admission scores (r = 0.371, p < 0.001) and mRS admission scores (r = 0.439, p < 0.001). At third month, fibrinogen levels were significantly related with NIHSS (r = 0.544, p < 0.001) and mRS (r = 0.538, p < 0.001) scores. Regression analysis revealed that a one-unit increase in fibrinogen levels resulted in a 0.018-unit increase in NIHSS scores and a 0.008-unit increase in mRS scores (p < 0.001). Elevated fibrinogen levels during the acute phase are related with poorer neurological outcomes and increased morbidity and mortality within the three-month follow-up period in patients with first-time ischemic stroke. These resultsindicate that fibrinogen could be considered a prognostic biomarker for stroke management and rehabilitation planning.